The Reconstruction of the Diocletianic Fortress in Babylon of Egypt: Architectural Decorations and Details - Karelin, Dmitry A. (Actual Problems of Theory and History of Art, 2019)
This paper is dedicated to the virtual reconstruction and the study of architectural ornaments and details of the Late Roman fortress of Babylon. This monument was located in the district now known as Old Cairo. The fortress has been explored and recorded since the end of the 19th century. From the 1990s onwards archaeological investigations have accompanied conservation works and the lowering of groundwater level in the area, and the results of these works were published in 2010. Babylon was a typical Diocletianic fortress for the field army, however it also possessed a number of unique features. First, it was constructed over the earlier Trajanic-era stone harbour at Babylon where the Amnis Trajanus joined the Nile. The entrance to the canal was flanked by massive round towers. Second, archaeological and historical evidence indicates that the bridge over the Nile led to the western gate of the fortress. Third, the sizeand strength of the fortifications were much more solid than those of any other Diocletianic fortress in Egypt. The recent archaeological work has shown that much of the southern part of fortress survives today under the ground. The southern gatehouse on the ground is largely intact, with the Coptic “Hanging Church” (Al-Mu’allaqa) built over it. The two round towers also survived, one of them within the Greek Orthodox Church of St. George (Mari Girgis). The aim of the reconstruction was to show the architectural and constructional features of the southern gatehouse and of the round towers flanking the Amnis Trajanus, and also to present the possible view of the fortress from the Nile. Another special aim was to classify the corpus of the sources of information and to show the connection between each source, as well as to visually present the arguments for the reconstruction. The aim of this paper is to examine and to give arguments for the reconstruction of the architectural decoration of the fortress, and to show their stylistic peculiarities. There are some details and decorations of special interest: the partly surviving cornice of the pediment of the southern gate, the capitals and cornices of the inner atriums in the round towers, the lion-headed mooring stones and the items which could be located in the apses of the round towers.